Detection of Mycobacterium leprae infection in family clusters from six leprosy-endemic regions in Colombia. (16th November 2021) - Serrano-Coll, Héctor; Osorio-Leal, Yuliana; Escobar-Builes, María Victoria; Cardona-Castro, Nora
Abstract: Background: Leprosy is a chronic infectious disease caused by Mycobacterium leprae, which continues to be endemic in tropical countries, making it necessary to implement strategies for its elimination. The objective of the current article was to detect M. leprae infection and associated factors through serological and epidemiological evaluation in family clusters of leprosy patients. Methods: Mycobacterium leprae infection was determined in 50 family clusters of leprosy patients from the departments of Bolívar, Atlántico, Santander, Boyacá, Chocó and Antioquia through the detection of antibodies (protein A, IgM, IgG) against anti-natural octyl disacharide-leprosy IDRI diagnostic (NDO-LID). Results: Higher seroconversion and elevated titers of these antibodies against NDO-LID were observed in the population of Chocó and Atlántico (p<0.05). Additionally, a higher frequency of infection was observed in large family groups that consumed armadillo meat and belonged to a low socioeconomic stratum (p<0.05). Multivariate analysis established that the main associated factors for a family cluster experiencing this infection were belonging to a vulnerable economic stratum and a large family group. Conclusions: This study found that the set of social and demographic variables (i.e. armadillo consumption, geographic area, low socioeconomic status and belonging to a large family cluster) are related to the promotion of seropositivity in family clusters.